Stressors and psychological well-being among students in a public university in Malaysia / Siti Rapidah Omar Ali, Nur Shafni Mohd Said and Khalid Amin Mat - Omar Ali, Siti Rapidah; Mohd Said, Nur Shafini; Mat, Khalid Amin (UiTM Cawangan Kedah, 2022)
Considerable stress can lead to range of issues that influence a student's well-being. Mental illness among youth is apparently a major problem worldwide nowadays. This study tried to examine the relationship between stressors namely academic stress, financial, social support, and environmental stress on psychological well-being among undergraduate students. A sample of 350 self-administered questionnaires were distributed to undergraduate students in a public university in East Coast of Peninsular Malaysia. The study has adopted convenience sampling method. Pearson correlation and regression analysis were used to predict the relationship and influence of all stressors towards psychological well-being. Finding shows that three factor of stressors elements have positive relationship with the psychological well-being. Meanwhile, social support indicates moderate, positive correlation with the psychological well-being. Academic stress has a minor beneficial affect on psychological well-being, according to multiple regression analysis, while social support has a moderately favourable influence. Multiple regression analysis displays that academic stress slightly positive influenced towards psychological well-being while social support has moderately positive influenced. Other two variables have been found negatively influenced psychological well-being. Hence, only hypothesis three and four were accepted while the other two were rejected.